Effects of copper/graphene oxide core-shell nanoparticles on Rhipicephalus ticks and their detoxification enzymes - Haytham Senbill; Amr Gangan; Ahmed M. Saeed; Mohammed E. Gad; Jehan Zeb; Alaa Fahmy (Scientific Reports)
Abstract Nanopesticides have been recently introduced as novel pesticides to overcome the drawbacks of using traditional synthetic pesticides. The present study evaluated the acaricidal activity of Copper/Graphene oxide core-shell nanoparticles against two tick species, Rhipicephalus rutilus and Rhipicephalus turanicus. The Copper/Graphene oxide core-shell nanoparticles were synthetized through the solution plasma (SP) method under different conditions. The nanoparticles synthesized at 180 W and 45 min were highly toxic to Rh. rutilus and Rh. turanicus, with 50% lethal concentration (LC50) values of 248.1 and 195.7 mg ml−1, respectively, followed by those which were synthesized at 120 W/30 mins (LC50 = 581.5 and 526.5 mg ml−1), 120 W/15 mins (LC50 = 606.9 and 686.7 mg ml−1), and 100/45 mins (LC50 = 792.9 and 710.7 mg ml−1), after 24 h of application. The enzyme assays revealed that 180 W/45 min treatment significantly inhibited the activity of acetylcholinesterase (115 ± 0.81 and 123 ± 0.33 U/ mg protein/min) and superoxide dismutase (290 ± 0.18 and 310 ± 0.92 U/ mg protein/min) in Rh. rutilus and Rh. turanicus, respectively, as compared with the negative control. The results also revealed a significantly increased catalase activity (895 ± 0.37 and 870 ± 0.31 U/ mg protein/min) in Rh. rutilus and Rh. turanicus, respectively. The above results indicated that Copper/Graphene oxide core-shell nanoparticles could be a promising alternatives for the management of ticks.